2019
DOI: 10.3389/fimmu.2019.02568
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression-Based Identification of Antigen-Responsive CD8+ T Cells on a Single-Cell Level

Abstract: CD8+ T cells are important effectors of adaptive immunity against pathogens, tumors, and self antigens. Here, we asked how human cognate antigen-responsive CD8+ T cells and their receptors could be identified in unselected single-cell gene expression data. Single-cell RNA sequencing and qPCR of dye-labeled antigen-specific cells identified large gene sets that were congruently up- or downregulated in virus-responsive CD8+ T cells under different antigen presentation conditions. Combined expression of TNFRSF9, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…Exhaustion consensus signature list was derived by considering genes that were present in > 3 exhaustion signature datasets (31,32,(40)(41)(42)(43)(44)(45)(46). Genes that were present in cytotoxicity signatures (40,102) or viral activation signatures (65) were excluded from the consensus list (table S5). The R package fgsea was used to calculate the GSEA scores with the signal-to-noise ratio as a metric.…”
Section: Gene Set Enrichment Analysis and Signature Module Scoresmentioning
confidence: 99%
“…Exhaustion consensus signature list was derived by considering genes that were present in > 3 exhaustion signature datasets (31,32,(40)(41)(42)(43)(44)(45)(46). Genes that were present in cytotoxicity signatures (40,102) or viral activation signatures (65) were excluded from the consensus list (table S5). The R package fgsea was used to calculate the GSEA scores with the signal-to-noise ratio as a metric.…”
Section: Gene Set Enrichment Analysis and Signature Module Scoresmentioning
confidence: 99%
“…To further understand the immune characteristics of the two groups. The ssGSEA method was used to further evaluate the immune-cell infiltration status of TCGA colorectal cancer transcriptome, and the results suggested that neutrophils, macrophage M1 cells, T cells, and CD4 memory resting cells were enriched in the low-risk group, while M0 cells and T cell regulatory cells were more common in the high-risk group, numerous studies have shown that dense infiltration of T cells, especially cytotoxic CD8 T cells, and high density of M1 macrophages may be associated with acute inflammation, suggesting a good prognosis ( Fuchs et al, 2019 ; Marcelis et al, 2020 ). In contrast, in many malignancies, M2 macrophages (the major subtype of macrophages) are associated with chronic inflammation and contribute to tumor growth and the development of aggressive phenotypes and have been associated with adverse outcomes ( Mantovani et al, 2002 ; Yamaguchi et al, 2016 ), and it is noteworthy that our findings support these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Combining TCR sequencing (or selection based on autoantigen reactivity), with scRNAseq has the potential to give further insights into T cell function. This has not always been straightforward to demonstrate, for example analysis of IGRP-specific T cells from the peripheral blood did not show a distinctive gene expression (GEX) pattern in response to stimulation (25). Similarly scRNAseq of ZnT8 reactive cells from the peripheral blood of people with T1D showed similar GEX profiles to healthy controls, indicating that these peripheral T cells may not be playing a driving role in T1D, although T1D patients had higher expression of aryl hydrocarbon receptor (AHR) and aurora kinase A (AURKA) and lower expression of RORA (26).…”
Section: Phenotypes Of Antigen-specific T Cells: Combining Tcr Sequencing With Gene Expressionmentioning
confidence: 99%